EFEKTIFITAS EKSTRAK BONGGOL NANAS (Ananas comosus L. Merr) TERHADAP Escherichia coli - Siti Juariah; Diana Wati (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2020)
Escherichia coli is one of the bacteria that lives in digestive system and could cause a diarrheal. Diarrheal treatment is done by using antibiotic. The use of antibiotic in continuous way could be affected the bacteria resistances toward antibiotic. However, the study on natural anti-bacterial substance is being carried out using pineapple hump. This study was aimed to determine the secondary metabolites that contain in pineapple hump and the inhibition test of Escherichia coli by using experimental laboratory method in vitro. Pineapple hump extract created in many concentrations are 10%, 15%, 20%, 25%, 40%, 60%, and 80%, after that inhibition test of Escherichia coli was done and it will be incubated during 1x24 hours. The result Shows that pineapple hump extract gain percentage of an inhibition test of Escherichia coli in concentrations 40%, 60%, and 80% are 50%, 63%, and 75%, compared with positive control and active compounds that contain in pineapple hump are bromelin, flavonoid, tannin, and saponin enzymes. This result could be concluded that pineapple extract hump potentially inhibit Escherichia coli which is marked by the formation of inhibitory zone.